A Comprehensive Review of SnSexTe1-x Chalcogenide Thin Films for Next-Generation Photovoltaics (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Global energy demand is projected to increase by nearly 1.5-fold by 2050, driven by fossil fuel depletion and the urgency of climate mitigation, thereby positioning thin-film photovoltaics as a critical component of sustainable energy transitions. This review traces the progression of solar-cell absorber materials-from crystalline silicon with efficiencies of ~27% and CdTe/CuInxGa1-xSe2 (CIGS) nanoparticle thin films with ~22%-toward earth-abundant chalcogenide ternaries such as SnSexTe1-x alloys. These materials exhibit tunable band gaps (0.9-1.5 eV), high absorption coefficients (>10⁵ cm⁻¹), and theoretical efficiencies approaching 36% in optimised heterostructures. However, experimental power conversion efficiencies remain limited to about 2.5%, primarily due to intrinsic defects, non-radiative recombination, and challenges in scalable fabrication. Drawing on 2024-2025 data from the Energy Institute and the International Renewable Energy Agency (IRENA), this analysis underscores the non-toxic and earth-abundant advantages of SnSexTe1-x, while contrasting them with the instability issues in perovskites and the phase complexity in kesterites. The review further highlights strategies such as bandgap engineering, atomic layer deposition (ALD)-based passivation, and multi-junction tandem architectures, along with scalable pulse laser deposition (PLD) routes, as promising approaches to achieving power conversion efficiencies exceeding 30%.